GERAKAN DEMO REFORMASI DIKORUPSI DALAM FOTO JURNAL DI JAKARTA - Malcheni Sangrawati; Erlina Novianti; Silviana Amanda Aurelia (Jurnal Dimensi DKV Seni Rupa dan Desain, 2022)
Photography journalistic is use as factual media in the form of visuals that provide interesting information. The Reform corruption demonstrations demanded the preparation (RKUHP) and RUU KPK. At the photo of the Corruption Reform Demonstration, the writer uses the theory of journalistic photography as a photo that is valuable for information as well as news and uses the EDFAT and Decisive moment methods. The research objective is to document the situation of the corruption demonstration that uses the EDFAT method in journalistic as well as providing factual information. The research method was carried out by observation. The author observed existing photos as well as literature studies for data collection. The results of the research are photo works that use journalistic by paying attention to the EDFAT method in the photo taking design, as well as the decisive moment theory in taking an appropriate event.  Keywords: Decisive moment, Democracy,  EDFAT,  Journalistic photography.